2022
DOI: 10.3390/ijerph19031657
|View full text |Cite
|
Sign up to set email alerts
|

Parasitological Assessment of Sewage Sludge Samples for Potential Agricultural Reuse in Tunisia

Abstract: Wastewater sludge represents an important resource for reuse in agriculture. However, potentially harmful pathogens are a main threat in this context. Thus, the aim of this study was to examine the presence of helminth ova and protozoan cysts in dried sewage sludge samples collected from ten wastewater treatment plants (WWTPs) located in eight governorates in Tunisia. Based on morphological criteria, protozoan cysts of Giardia spp., Entamoeba histolytica/dispar/moshkovskii, and Entamoeba coli, were detected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…These findings are similar with the studies of. 38,53,54 Simultaneously, the present results are compatible with those of 42,55,56 who reported that A. lumbricoides ova were the most abundant in the MWTP s samples. Generally, the conventional activated sludge system and oxidation ditches were showed to be efficient in the removal of A. lumbricoides and H. nana ova with removal efficiency of 100%.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are similar with the studies of. 38,53,54 Simultaneously, the present results are compatible with those of 42,55,56 who reported that A. lumbricoides ova were the most abundant in the MWTP s samples. Generally, the conventional activated sludge system and oxidation ditches were showed to be efficient in the removal of A. lumbricoides and H. nana ova with removal efficiency of 100%.…”
Section: Discussionsupporting
confidence: 92%
“…Another study in Tunisia also discovered 56.9% of Ascaris spp. eggs in sewage sludge (17). This discovery is also related to research in which helminth eggs were more frequently discovered in sludge in developing nations, where the concentrations can range from 7 to 80 times greater than in developed countries (4).…”
Section: Discussionmentioning
confidence: 83%
“…In another study carried out in West Bengal, India, the Ascaris species was the most predominant parasitic ova observed 29 . Ascaris species which is a roundworm affects about a quarter of the world's population 30 , It is one of the resistant intestinal infections that is frequently employed as a parasitological indicator 31 and is more common in developing countries 30 . The possession of a thick outer covering (cuticle) made Ascaris species more resistant to adverse environmental conditions and provides them with a long span in the soil 32 .…”
Section: Discussionmentioning
confidence: 99%